The Emergence of Digital Platforms: A Conceptual Platform Architecture and impact on Industrial Engineering. (October 2019) - Zutshi, Aneesh; Grilo, Antonio
Abstract: The Digital Platform Business Model has caused massive disruption across multiple industries and services and led to optimising efficiencies, speeding up information sharing and dynamising of business processes. This new phenomenon has pushed businesses into redesigning their strategy, and enabled economies of scale for several smaller companies, through the evolution of Business Ecosystems based on Digital Platforms. In this paper, through a systematic analysis of numerous case scenarios, we present a conceptual understanding of the Digital Platform and explore its impact in the field of Industrial Engineering as well as its implications for society. We elaborate on the key actors and characteristics of a Digital Platform Ecosystem and identify its main Value Proposition. We also present a Digital Platform Architecture, that enables us to conceptually classify its various layers based on the functionality and domain knowledge. Finally, we elaborate on the impact of Digital Platforms on Industrial Engineering, and identify scenarios where different areas of Industrial Engineering can be applied to the different layers of our Digital Platform Architecture.